Cold Plasma as a Novel Pretreatment to Improve the Drying Kinetics and Quality of Green Peas - Jun-Wen Bai; Dan-Dan Li; Reziwanguli Abulaiti; Manqian Wang; Xiaozhi Wu; Zhenwei Feng; Yutong Zhu; Jianrong Cai (Foods)
Green peas, with their high moisture content, require effective drying techniques to extend shelf life while preserving quality. Traditional drying methods face challenges due to the dense structure of the seed coat and wax layer, which limits moisture migration. This study investigates cold plasma (CP) pretreatment as a novel approach to enhance drying kinetics and maintain the quality attributes of green peas. The results showed that CP treatment significantly improves drying efficiency by modifying the pea epidermis microstructure, reducing drying time by up to 18.18%. The moisture effective diffusivity coefficients (Deff) for untreated and CP-pretreated green peas were calculated to range from 5.9629 to 9.9172 × 10−10 m2·s−1, with CP pretreatment increasing Deff by up to 66.31% compared to the untreated group. Optimal CP parameters (90 s, 750 Hz frequency, 70% duty cycle) were found to improve the rehydration ratio, preserve color, and increase total phenolic content (TPC) by 24.06%, while enhancing antioxidant activity by 29.64%. Microstructural changes, including pore formation and increased surface roughness, as observed through scanning electron microscopy (SEM), partially explain the enhanced moisture diffusion, improved rehydration, and alterations in nutrient content. These findings underscore the potential of CP technology as a non-thermal, eco-friendly pretreatment for drying agricultural products, with broad applications in food preservation and quality enhancement.